Farmer evaluation of an advanced cowpea line for agronomic performance in eastern Uganda (Makerere University Journal of Agricultural & Environmental Sciences, 2003)
The study explored farmers' assessment of the new improved cowpea line MU-93 against a local cultivar (Ebelat) in terms of yield, pest and disease resistance and farmers' preference for home consumption and market. The study was carried out within the Integrated Pest Management (IM) Farmer Field School environment where the advanced cowpea line MU-93 was used as a resistant component of a cowpea IPM package. The yields of MU-93 were markedly higher than those of Ebelat; unsprayed MU-93 yielded higher than Ebelat, even when Ebelat was sprayed weekly. MU-93 had higher germination percentage, better growth vigor, high leaf and pod production as well as good grain taste. In addition MU-93 had lower pest and disease infestation, higher grain yield, good seed quality and higher market preference. However, it is a late maturing line compared to Ebelat, and after the budding stage its leaves and pods were considered relatively unpalatable.MU-93 also produces fewer but longer pods with bigger grains than Ebelat. Ebelat had moderate germination percentage, early maturity, and had good leaf taste. Basing on the farmers' positive assessment, MU-93 has been submitted to the Uganda Variety Release Committee for possible national release.
Keywords: Farmer field school; integrated pest management; Uganda; Vigna unguiculata